Public and Private Sector to Zero Deforestation Commitmen in South Sumatra - Ristiana, N.I.; Purnomo, H.; Hero, Y.; Okarda, B.; Puspitaloka, D.; Sanjaya, M. (Institut Pertanian Bogor, 2022)
To address deforestation, South Sumatra Goverment was committed to be the frontrunner in attaining Green Growth 2017. All economic activities related to land use must comply with the regulations. The private sector supports them with some initiatives by several certifications as their commitment toward zero deforestation (ZDC). However, from the land cover data, South Sumatra Province is one of the highest forest cover loss in Indonesia followed by increasing economic activities. This study aims to explain commitments of the public and private sectors in complying toward zero deforestation. We conducted interviews with relevant agencies and collect the data regarding interventions and initiatives. This study used compliance theory to analyze the commitments of both sectors. The results showed that the public and private sectors in South Sumatra have shown their commitment with the type of treaty-induced compliance. The compliance showed how the commitment is integrated into policies, aligned public and private governance arrangements, and a good environmental quality change by reduced deforestation rate. This showed that one of the ZDC’s objectives is at least halve the rate of loss of natural forests globally by 2020 has been implemented by both. Thus, they strive to end natural forest loss by 2030.